Antimicrobial-resistant infections among postpartum women at a Ugandan referral hospital - Bebell, Lisa M.; Ngonzi, Joseph; Bazira, Joel; Fajardo, Yarine; Boatin, Adeline A.; Siedner, Mark J.; Bassett, Ingrid V.; Nyehangane, Dan; Nanjebe, Deborah; Jacquemyn, Yves; Geertruyden, Jean-Pierre van; Mwanga-Amumpaire, Juliet; et al. (PLOS ONE, 2017)
Puerperal sepsis causes 10% of maternal deaths in Africa, but prospective studies on incidence, microbiology and antimicrobial resistance are lacking. Methods We performed a prospective cohort study of 4,231 Ugandan women presenting to a regional referral hospital for delivery or postpartum care, measured vital signs after delivery, performed structured physical exam, symptom questionnaire, and microbiologic evaluation of febrile and hypothermic women. Malaria rapid diagnostic testing, blood and urine cultures were performed aseptically and processed at Epicentre Mbarara Research Centre. Antimicrobial susceptibility and breakpoints were determined using disk diffusion per EUCAST standards. Hospital diagnoses, treatments and outcomes were abstracted from patient charts. Results Mean age was 25 years, 12% were HIV-infected, and 50% had cesarean deliveries. Approximately 5% (205/4176) with _1 temperature measurement recorded developed postpartum fever or hypothermia; blood and urine samples were collected from 174 (85%), and 17 others were evaluated clinically. Eighty-four (48%) had at least one confirmed source of infection: 39% (76/193) clinical postpartum endometritis, 14% (25/174) urinary tract infection (UTI), 3% (5/174) bloodstream infection. Another 3% (5/174) had malaria. Overall, 30/174 (17%) had positive blood or urine cultures, and Acinetobacter species were the most common bacteria isolated. Of 25 Gram-negatives isolated, 20 (80%) were multidrug-resistant and cefepime non-susceptible. Conclusions For women in rural Uganda with postpartum fever, we found a high rate of antibiotic resistance among cultured urinary and bloodstream infections, including cephalosporin-resistant Acinetobacter species. Increasing availability of microbiology testing to inform appropriate antibiotic use, development of antimicrobial stewardship programs, and strengthening infection control practices should be high priorities.
Keywords: Antimicrobial; Resistant infections; Postpartum; women; Ugandan